Bird species diversity, abundance and distribution in Ulot Watershed, Can-avid, Eastern Samar - Jocosol, Ma. Joy O. (2016)
This study was conducted to identify the species, diversity, richness, abundance and distribution of birds in Ulot Watershed, Can-avid, Eastern Samar. The avifaunal species were observed from January to April 2016. Ten station points were established using the point count method. Data gathered were analyzed according to species abundance, species richness and species diversity index. A total of 1021 individuals were recorded that belongs to 58 different species under 28 families. Out of these, 31 species are endemic, 21 are residents, while 6 are migrants. Passer montanus was the most frequently encountered species (96 counts). Station point in Baras has the highest species richness (D=2.337). The bird species observed represent 8.6% and 18.71% of the total known bird species in the Philippines and Samar, respectively. Furthermore, this study identified 14 new species of birds not previously listed in Eastern Samar. The presence of these birds revealed that Ulot Watershed provides habitat for several bird species. It is therefore important to focus on conservation on the habitat and avifaunal resources in the sites to cater other bird species, especially, those that are endemic and globally threatened.